Ex-Post Impact Evaluation of an Export Promotion Matching Grant : Tunisia's Second EMAF - Gourdon, J.; Marchat, J.M.; Sharma, S.; Vishwanath, T. (World Bank, Washington, DC, 2012)
Among the root causes of the current political turmoil in the Middle East and North Africa (MENA) region are the large numbers of unemployed but increasingly educated youth. For the region to achieve stability, it will have to ensure a more inclusive and faster growth path and find enough jobs for this cohort. Exports will play a key role in moving in this direction and this fast brief examines the impact of Matching Grants (MG) in supporting exports. This quick note is another addition to this body of work and presents results from one of the first ex-post Impact Evaluation (IE) of an active export promotion MG in a middle income country, Tunisia. This IE was undertaken in preparation of a lending operation. Finally, it must be noted that with the matching process, the untreated group with high propensity score will be more used for comparison than those with low propensity score so this will give more weight to firms that were 'targeted' by second Export Market Access Fund (EMAF). Hence it is key to see if the firms especially targeted by second EMAF would have done better or worse without the support.